A study on spatio-temporal coordination and driving forces of urban land and water resources utilization efficiency in the Yangtze River Economic Belt. Issue 1 (19th December 2022) - Li, Zhenqiang; Guo, Jiayao; You, Xiaoyue
Abstract: Using panel data from 11 provinces from 2003 to 2017 in the Yangtze River Economic Belt, the study explores the spatio-temporal differentiation characteristics and driving forces of coupling coordination of urban land and water resource utilization efficiency by constructing the coupling coordination model and the spatial econometric model. The results show that (1) in terms of time, the situation of inefficient utilization of urban land and water resources was severe. Spatially, the distribution of utilization efficiency of two resources was consistent with the pattern of regional economic development; (2) the coupling coordination degree of urban land and water resources utilization efficiency was mainly of mild disorder type and transitional type, and was in a gradient decreasing spatial distribution from downstream to midstream to the upstream region; (3) the coupling coordination degree of urban land and water resources utilization efficiency presented significantly positive spatial auto-correlation, but the agglomeration trend was weakening; (4) per capita GDP, employment labor force and fixed assets investment were important driving forces for the coordination development of urban land and water resources, while the role of government and the total population had a negative impact on it, and the driving role of the industrial structure had not yet been played. HIGHLIGHTS: This study analyzes the spatio-temporal differentiation characteristics of urban land and water resources utilization efficiency. This study explores the driving forces of coupling coordination degree of urban land and water resources. This study makes it possible to point out the weak factors, so as to improve the related strategies to help build a harmonious relationship between urban land and water resources.